Pengaruh Pendapatan Premi, Hasil Underwriting, Beban Operasional Dan Hasil Investasi Terhadap Laba Pada Perusahaan Asuransi Umum Yang Terdaftar Di BEI Periode Tahun 2017-2019 - Nur Maisunatul Aflachiyah Al awwaliyah; Abdul Kodir Djaelani; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of this study is to see the relationship between premium income (X1), underwriting results (X2), operating expenses (X3) and investment returns (X4) to profit (Y). The type of research used is descriptive quantitative research which functions to explain the effect of independent variables, namely premium income, underwriting results, operating expenses and investment returns on the dependent variable, namely profit using numbers starting from data, data interpretation and the appearance of the results, and data obtained through quantitative approach, namely in testing using numbers with statistical techniques. The sample selection technique uses a purposive sampling technique with criteria included in general insurance companies listed on the Indonesia Stock Exchange from 2017-2019, general insurance companies that issue or publish annual reports in a row during 2017-2019 and companies who published their annual reports for the end of December 31, in order to obtain 13 general insurance companies. The data analysis technique used in this research is normality test, classic assumption test, multiple linear regression test and hypothesis testing. From data management, it is found that premium income, underwriting results and investment returns have a significant effect on profits, while operating expenses are not significant. And simultaneously the variables have a significant effect on profit. Keywords: premium income, underwriting results, operating expenses, investment returns and profits.